CAFF CBMP Report No.13 - A Strategy for Facilitating and Promoting Community-Based Monitoring Approaches in Arctic Biodiversity Monitoring - Huntingdon, Henry (Conservation of Arctic Flora anf Fauna Working Group (CAFF), 2008)
Arctic Council's CAFF Working Group Circumpolar Biodiversity Monitoring Program Report No.13 - A Strategy for Facilitating and Promoting Community-Based Monitoring Approaches in Arctic Biodiversity Monitoring